Gairaigo in The Covid-19 Pandemic Era: A Study of Transformational Generative Phonology - S, Irzam Sarif; Risagarniwa, Yuyu Yohana; Sunarni, Nani (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2021)
Transformational Generative Phonology is a phonological theory that treats the distinguishing feature as the smallest unit and connects the distinguishing features and lexicons with phonological rules. This research has been conducted by several previous researchers, but study regarding the object in the Covid-19 pandemic is still limited. The purpose of this study was to explain the phonological process and phonological rules of foreign loan words into Japanese using transformational generative phonological approach. This study used descriptive qualitative method. Sources of the data were obtained from vocabularies or terms that appeared during the Covid-19 period. The results of this study indicated that there were six phonological rules which include, 1) the addition of the phoneme [u] at the end of words; 2) the addition of the phoneme [o] at the end of the word; 3) Addition of phoneme [u] in the middle of the word, 4) Addition of phoneme [o] in the middle of the word; 5) Addition of phoneme [k] at the end of the word, and; 6) Substitution of phoneme [l] to [r]. So that the implementation of this research was to create a rule to make it easier for foreign learners of Japanese to understand the sound changes that occur in Japanese lingual units.